ANALISIS PENGGUNAAN APLIKASI TERJEMAHAN DI INDONESIA MENGGUNAKAN METODE STATISTIKA - Dendi; Topiq, Salman; Aulias, Moch Rafki (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
In the increasingly advanced era of globalization and digitalization, the need to understand foreign languages is very important. Indonesia, which has a lot of linguistic diversity, also has difficulty communicating between people. For this reason, there is a lot of technology in the form of Indonesian translation applications which is very useful for users communicating with each other. The aim of this research is to analyze how many regional language translation application users there are in Indonesia, the level of satisfaction, and translation accuracy in translation applications using statistical methods. Apart from that, the methodology used, namely data collection in the form of a survey followed by statistical analysis, was also carried out in the research. It is also hoped that with this research, translation applications in Indonesia can develop for the better